PERHITUNGAN DAN PENAGIHAN PAJAK KENDARAAN BERMOTOR RODA DUA (2) MERK YAMAHA PADA BADAN PENDAPATAN DAERAH PROVINSI SULAWESI SELATAN - Lina Mariana; Yola Miranda (Jurnal Riset Perpajakan: Amnesty, 2020)
This study aims to determine the system of calculation and tax collection of two-wheeled motor vehicles (2) at the Regional Revenue Agency (BAPENDA) of South Sulawesi Province. The study was conducted for two months from January to February 2020. This research used a descriptive method with a qualitative approach. The type of data used is primary data and secondary data. Data collection is done by interview and documentation. The results showed the calculation system of Motorized Vehicle Tax (2) of Yamaha Brands in the Regional Revenue Agency (BAPENDA) of South Sulawesi Province, namely the Selling Value of Motor Vehicles at times with PKB rates. And the motor vehicle tax collection system at the Regional Revenue Agency is through the Samsat office.